Coenopopulations of clone forming subshrub plants in forest ecosystems of Desnyansko-Starogutsky National Nature Park - Коваленко, І. М. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
Ontogenetic pattern of three species of subshrub layer in forest ecosystems of Desnyansko-Starogutsky National Nature Park has been studied: Calluna vulgaris (L.) Hull. – in 3 associations, Vaccinium myrtillus L. – in 5 associations, Vaccinium vitis-idaea L. – in 4 associations. The conclusions on status of cenopopulations have been made based on a sample of 12.321 partial bushes. Monomodal cenopopulations with one population peak prevail among the investigated cenopopulations in forest ecosystems. Cenopopulations of C. vulgaris were equally not full-membered, but differed in the nature of age spectra. Coenopopulation of C. vulgaris was the youngest one (the aging index of cenopopulation is 0.09 only) in the association of Pinetum callunoso-hylocomiosum. All five populations of V. myrtillus with the different aging indices had the similar indices of generativity at the level of 41–54 %. All of the investigated cenopopulations of cowberries were not full-membered, monomodal, but peaks of the age spectra were in different areas because of different age of populations of V. vitis-idaea. The vast majority of coenopopulations of clone forming plants of grass and subshrub layer have turned out to be the centered ones with the population peak, which accounts for generative species.